Enhancing primary school leadership through cultural intelligence and talent management: a case study approach - Hughes, James; Davis, Kate (Sage, 2025)
This study addresses the challenge of sustaining effective primary school leadership in contexts of high accountability, limited resources, and staff turnover. The research examines how cultural intelligence, structured team dynamics, and strategic talent management can enhance leadership effectiveness and support school improvement. Drawing on a qualitative case study of a two-form entry primary school in Surrey, England, data were collected from performance management records, appraisal documentation, strategic planning documents, and leadership reflections. Thematic analysis identified how cultural alignment, collaborative structures, and internal talent pipelines improved staff engagement, retention, and professional growth. Findings show that leadership practices grounded in cultural intelligence and distributed responsibility fostered resilience, creativity, and collective efficacy among staff. The study contributes to the literature by demonstrating how these frameworks can be operationalized in primary schools. Practical implications include reevaluating inspection frameworks and leadership standards so they value cultural work, collaborative practice, and leadership-pipeline development as drivers of sustained school improvement.
Keywords: Education; 3904 Specialist studies in education; Educational leadership; cultural intelligence; team dynamics; talent management; school improvement; staff development; primary education